2006
DOI: 10.1038/sj.emboj.7601396
|View full text |Cite
|
Sign up to set email alerts
|

The BAH domain facilitates the ability of human Orc1 protein to activate replication origins in vivo

Abstract: Selection of initiation sites for DNA replication in eukaryotes is determined by the interaction between the origin recognition complex (ORC) and genomic DNA. In mammalian cells, this interaction appears to be regulated by Orc1, the only ORC subunit that contains a bromo-adjacent homology (BAH) domain. Since BAH domains mediate protein-protein interactions, the human Orc1 BAH domain was mutated, and the mutant proteins expressed in human cells to determine their affects on ORC function. The BAH domain was not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
91
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 57 publications
4
91
1
Order By: Relevance
“…To determine whether or not HsOrc6 in its native environment is bound to a nuclear transport protein, FH-Orc6 was purified by double affinity chromatography from HeLa cells that expressed it constitutively. Previous applications of this strategy demonstrated that constitutively expressed FH-Orc1 and FHOrc2 proteins modeled their endogenous counterparts (8,9). They are assembled into ORCs in the nuclei of G 1 -phase cells where they preferentially bind to DNA replication origins and stimulate DNA replication.…”
Section: Orc6mentioning
confidence: 99%
See 2 more Smart Citations
“…To determine whether or not HsOrc6 in its native environment is bound to a nuclear transport protein, FH-Orc6 was purified by double affinity chromatography from HeLa cells that expressed it constitutively. Previous applications of this strategy demonstrated that constitutively expressed FH-Orc1 and FHOrc2 proteins modeled their endogenous counterparts (8,9). They are assembled into ORCs in the nuclei of G 1 -phase cells where they preferentially bind to DNA replication origins and stimulate DNA replication.…”
Section: Orc6mentioning
confidence: 99%
“…Mammalian ORC(2-5) can assemble spontaneously in vitro from individual ORC subunits under a variety of conditions (7)(8)(9)(10)(11)(12)(13)(14). Assembly begins with formation of an ORC(2, 3, 5) complex to which Orc4 binds in a manner that requires binding of ATP to both the Orc4 and Orc5 subunits (11,12) (Fig.…”
Section: Nuclear Localization Of Orc6-humanmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the ORC subunits in eukarya, only Orc1 has a BAH domain that mediates protein -protein interactions. The BAH domain in human Orc1 facilitates the ability of Orc1 to activate replication origins in vivo (Noguchi et al 2006), and links H4K20me2 to DNA replication licensing and the Meier-Gorlin syndrome, primordial dwarfism that is related directly to mutations in prereplication proteins (Bicknell et al 2011;Kuo et al 2012).…”
Section: Dna Replication Proteins the Prereplication Complexmentioning
confidence: 99%
“…The BAH domain of ORC1 is important for the activation of EBNA1-dependent origins of DNA synthesis. Deletion of the entire domain (AA1-169), as well as a single point mutation (E111K), reduced the association of ORC1 with DS to background as measured by Chromatin ImmunoPrecipitation (ChIP) (Noguchi, Vassilev et al 2006). These same modifications also reduced the short-term replication of oriP plasmids to background levels, and the overexpression of the BAH domain alone (AA 1-315) functioned dominant-negatively to inhibit oriP replication (ibid).…”
mentioning
confidence: 99%